Similarity Index of Doctoral Theses Submitted to Universities in Kerala: An investigation - SURESH KUMAR PK (Library Philosophy and Practice (e-journal), 2019)
Plagiarism has grown to such an alarming rate that the academic community finds it difficult to spot an authentic work among the plethora of published literature. Anti- plagiarism softwares have become popular as a solution to overcome this problem. This study aims to describe various aspects of plagiarism, to assess the contribution of PhD theses in ShodhGanga by the universities in Kerala, to identify the subject wise contribution of PhD theses in various universities in Kerala during 2010-17,to find the extend of similarity of content in the PhD theses of the Universities in Kerala and to rank the universities in Kerala with respect to the similarity index. The study is based on 70 PhD theses of three Universities in Kerala viz. University of Kerala, M.G University and University of Calicut selected at random by simple random sample method from the theses available in shodhGanga. The theses selected were tested by using Urkund, anti-plagiarism software maintained by INFLIBNET. It was found that Science subjects show least similarity index whereas Social Science subjects have the highest similarity rate. Faculty of Arts (26.6%) has a high degree of similarity followed by Humanities (26%) and lowest in Science (16%).Among the Universities University of Calicut occupied the top position with 21 % similarity index in its PhD theses followed by M.G University having 20.4% and the University of Kerala has least with 17.9% of similarity index. The paper points out the importance of user awareness programmes and training programmes on anti-plagiarism for the research guides, research scholars and library staff members.